Organizational development of agro-industrial complex on basis of cooperation and integration - Ivanov, S.; Perebyynis, V.; Oleksenko, L.; Svitlychna, A. (Економічний вісник Донбасу, 2016)
Expediency of organizational development of the agro-industrial complex of the economy on the principles of cooperation and integration has been proved. This allows to improve organizational and economic relations between enterprises of the agriculture and food industry. Two approaches have been grounded: the first is based on the developed raw material basis; the second is limited with a lack of agricultural raw materials. The model of cooperation of agricultural enterprises and enterprises of the food industry has been formed. Доведено доцільність організаційного розвитку агропродовольчого комплексу економіки на засадах кооперації та інтеграції. Це дозволяє удосконалити організаційно-економічні зв’язки між підприємствами сільського господарства та харчової промисловості. Обґрунтовано два підходи: перший, що ґрунтується на розвиненій сировинній базі; другий, що обмежений недостатньою кількістю сільськогосподарської сировини. Сформована модель кооперації сільськогосподарських підприємств і підприємств харчової промисловості. Доказана целесообразность организационного развития агропродовольственного комплекса экономики на основе кооперации и интеграции. Это позволяет усовершенствовать организационно-экономические связи между предприятиями сельского хозяйства и пищевой промышленности. Обосновано два подхода: первый, основанный на развитой сырьевой базе; второй, ограниченный нехваткой сельскохозяйственного сырья. Сформирована модель кооперации сельскохозяйственных предприятий и предприятий пищевой промышленности.